2020
DOI: 10.1177/1071100720966332
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Term Results of Corticosteroid Injections for Morton’s Neuroma

Abstract: Background: The objective of this study was to evaluate the medium-term results of corticosteroid injections for Morton’s neuroma. Methods: This was a prospective follow-up study of a previous randomized controlled trial (RCT). Forty-five neuromas in 36 patients were injected with a single corticosteroid injection either with or without ultrasound guidance. As the results of the RCT showed no difference in outcomes between techniques, the data were pooled for the purpose of this study. Questionnaires were sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Telemedicine has increasingly been used in many areas of surgery, including cancer 17,18 and orthopaedic arthroplasty care, 16 for postoperative care, monitoring of chronic conditions, and as a research tool in collating patient-reported outcomes. 4,8 Several studies have evaluated the impact of remote consultations for orthopaedic patients, 3,11 but have not reviewed the decision-making efficacy. Marsh et al evaluated the economic costs and benefits of follow-up with web-based radiographs, compared with in-person follow-up after arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine has increasingly been used in many areas of surgery, including cancer 17,18 and orthopaedic arthroplasty care, 16 for postoperative care, monitoring of chronic conditions, and as a research tool in collating patient-reported outcomes. 4,8 Several studies have evaluated the impact of remote consultations for orthopaedic patients, 3,11 but have not reviewed the decision-making efficacy. Marsh et al evaluated the economic costs and benefits of follow-up with web-based radiographs, compared with in-person follow-up after arthroplasty.…”
Section: Discussionmentioning
confidence: 99%